A Rule-based Mobile Application for Diagnosing Pet Disease: Design and Implementation - Ling Li Ng; Hanayanti Hafit; Ruhaya Ab. Aziz; Nur Liesa Mohammad Azemi; Siti Hawa Anurddin (Politeknik Negeri Padang, 2023)
Animals kept in homes for personal enjoyment rather than for work or sustenance are typically referred to as